En el nombre del otro: Cristianismo y pueblos originarios en la región chaqueña argentina (1965-1994) - Leone Jouanny, Miguel (Entre los libros de la buena memoria, 2022)
In the name of the other: Christianity and Indigenous peoples in the Argentine Chaco region (1965-1994). Pastoral aborigen ("aboriginal pastoral") is a type of ecclesiastical indigenism with Christian roots and an ecumenical perspective which, unlike other indigenist missions, did not seek to convert Indigenous people to Christianity, but rather to promote their development and contribute to their liberation. Pastoral aborigen missions were part of the conciliar renewal and were fraught with developmental precepts and leftist ideologies of the time. This book analyzes a particular case of this collective subject: the social network created in the late sixties and early seventies in the area that covers the center and west of the province of Formosa and the west of the province of Chaco (Argentina).